The Influence of Tradition Based Contextual Islamic Religious Education Learning on the Learning Outcomes of Tenth Grade Students at Muhammadiyah Vocational High School Pangkalan Balai - Yeni Yeldia Nopita Sari Sulaiman; Karoma; Arvin Efriani (STKIP Subang, 2026)
This study aimed to determine the effect of contextual Islamic Religious Education (PAI) learning based on local traditions on the learning outcomes of tenth-grade students at SMK Muhammadiyah Pangkalan Balai. The study employed a quantitative approach using an experimental method with a One Group Pretest Posttest Design. The population consisted of all tenth-grade students, while the sample was the tenth-grade students of the Office Management and Business Services (MPLB) class, totaling 35 students. Data were collected through tests, observation, and documentation. Data analysis was conducted using normality tests and paired sample t-tests with IBM SPSS. The findings revealed that both pretest and posttest data were normally distributed, with significance values of 0.528 and 0.349 > 0.05, respectively. The hypothesis testing showed a significance value of 0.000 < 0.05, indicating that contextual PAI learning based on local traditions had a significant effect on students’ learning outcomes. The students’ mean score increased from 51.68 in the pretest to 88.80 in the posttest. Therefore, contextual PAI learning based on local traditions proved effective in improving students’ learning outcomes through meaningful, contextual, and culturally relevant learning experiences.